Unification of processes in production lines in a factory environment: An application of time and motion study - Río, Daniel Guzmán del; Oliveira , Fernanda Carla dos S. de; Pacheco , Lucas Martins; Martins, Karolayne Barbosa; Silva, Andreia Vasconcelos da; Assis, Daniel Benício de; Soares, Daniel de Farias; Printes, André Luiz; Torné, Israel Gondres (Seven Editora, 2023)
The study of time and motion in the production lines of companies has become important to increase the productivity of companies today in times of Industry 4.0. In this work, which aims to present the unification of processes in production lines in a manufacturing environment of an industry in the Industrial Pole of Manaus - PIM, the authors address the concepts and fundamentals of the "Time and Motion Study"; it examines in detail the movements of workers, machines and equipment and the accounting of time required to do certain activities within the production process, to ensure the optimization of the process. Finally, the reduction of cycle time, optimization of line capacity, and the balancing ratio are presented.  DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-162